Ηidden homelessness and poverty trajectories in rural areas: stories of crisis counterurbanization in Greece - Anthopoulou, Theodosia; Partalidou, Maria; Kourachanis, Nikos (The Greek Review of Social Research, 2019)
The article examines invisible deprivation and housing precariousness in the countryside through the phenomenon of counterurbanization as a vehicle for overcoming poverty phenomena of urban households in Greece during the economic crisis. We argue that, despite the idealized picture for living in a village, as shown in the predominantly public discourse; rural life is governed by equally unfavorable living conditions for households at the risk of poverty. Through the theoretical framework of hidden homelessness in the rural, fundamental dimensions of housing problems and inadequate living conditions in the countryside are presented. Through the analysis of the different life pathways of people returning from the city to the village, the housing and social living conditions, during the crisis, in the Greek countryside are empirically examined. In the conclusions we find that returning back to rural areas, without accompanying established social support policies, only leads to the reproduction of a situation of proletarianization of households and to the transformation of urban poverty to rural poverty.